1984
DOI: 10.1021/ma00138a033
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and characterization of heteroatom-bridged metal-free phthalocyanine network polymers and model compounds

Abstract: Procedures for the preparation of metal-free phthalocyanine network polymers from oxygen-, sulfur-, and selenium-bridged bis(phthalonitrile) monomers were investigated on the basis of phthalocyanine model compounds derived from phenoxy-, (phenylthio)-, and (phenylseleno) phthalonitrile compounds. The oxygen-and sulfur-substituted phthalonitrile compounds could be converted in high yield to the corresponding metal-free phthalocyanine compounds by reaction with tetrahydropyridine, hydroquinone, or 4,4'-biphenol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(146 citation statements)
references
References 10 publications
4
142
0
Order By: Relevance
“…Also the OH protons of 2 are observed as broad signals at 11.83 and 4.87 ppm. As a consequence of the asymmetrical structure, the 13 C NMR spectrum of 2 shows eight different signals for the unsaturated carbon atoms, two arising from C ϵ N (116.31 and 110.79 ppm). The aliphatic carbon atoms also give two different signals at 59.28 and 32.49 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the OH protons of 2 are observed as broad signals at 11.83 and 4.87 ppm. As a consequence of the asymmetrical structure, the 13 C NMR spectrum of 2 shows eight different signals for the unsaturated carbon atoms, two arising from C ϵ N (116.31 and 110.79 ppm). The aliphatic carbon atoms also give two different signals at 59.28 and 32.49 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric phthalocyanines are interesting compounds that exhibit qualities as catalysts and semiconductors [10]. Much attention has been paid to the preparation and characterization of new phthalocyanine polymers which can be classified into those containing backbones in which phthalocyanine units are bound through peripheral reactive functional groups [11,12], and network polymers formed by cyclotetramerization of tetranitriles [13], tetracarboxcylic acid [14], etc. [15].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Weak absorptions for -C=N-at 1645 cm −1 for 4 and at 1652 cm −1 for 4a were also detected. Microanalyses for 4 and 4a were satisfactory.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…However, peak assigned to characteristic absorptions representative of phthalocynine (1010 cm -1 ) [33] formation can be hardly found. Additionally, the peak of nitrile group became weaker gradually with the curing degree, and there was still residual nitrile group even after post-cured of 3BOCN/[EPy]BF 4 system, which may due to the steric hindrance of the unreacted nitrile groups at the ortho-position of triazine ring [34]. Figure 7 showed the probable curing mechanism of 3BOCN/ [EPy]BF 4 system.…”
Section: Properties Of Polymer Network 321 Ft-irmentioning
confidence: 98%
“…On the other hand, although the content of ILs in Resin-2 (20% mass fraction) was the double of Resin-1 (10% mass fraction), the aging results showed that the long-term oxidative stability of Resin-2 was close to Resin-1 and even better, this phenomenon indicated that PN resins cured by ILs in proper content could bear long-term aging at high temperature under air. Another important aspect of PN resins is their water absorption capability [34]. Samples of Resin-1 and Resin-2 were dried in a vacuum oven at 120°C for 24 h before water absorption studies.…”
Section: Long-term Aging and Water Absorption Capabilitymentioning
confidence: 99%